Surgical Ventricular Restoration (SVR) for Ischemic Heart Failure - Chanda, PK; Sharifuzzaman, M; Ali, S; Haque, T; Ahmed, F (Cardiovascular Journal, 2010)
Surgical ventricular restoration (SVR) is a surgical procedure developed in an attempt to reverse the negative remodeling that occurs following myocardial infarction. SVR has evolved from a treatment for ventricular aneurysms and has become a treatment of ischemic heart failure.SVR procedure is usually performed after coronary artery bypass grafting (CABG) and may proceed or be followed by mitral valve repair or replacement. This article will review the procedure. Keywords: Surgical Ventricular Restoration; CABG; Mitral valve repair. DOI: 10.3329/cardio.v2i2.6646 Cardiovasc. j. 2010; 2(2) : 227-235